Pericytes or Mesenchymal Stem Cells: Is That the Question? - Cano-Rincón, Elena; Gébala, Véronique; Gerhardt, Holger (Elsevier, 2017)
For almost a decade, mesenchymal stem cells (MSCs) were believed to reside as perivascular cells in vivo. In this issue of Cell Stem Cell, Guimarães-Camboa et al. (2017) challenge this idea and use lineage tracing to demonstrate that perivascular cells do not behave as tissue-specific progenitors in various organs, despite showing MSC potential in vitro.
https://openpolicyfinder.jisc.ac.uk/id/publication/6583
Keywords: Sistema cardiovascular; Citología; Células madre; Pericytes; Mesenchymal stem cell